Frequent users of Mental Health Liaison Services within Emergency Departments. (December 2017) - Beck, Alison; Sanchez-Walker, Emma; Evans, Lauren J.; Harris, Victoria; Pegler, Ruth; Cross, Sean
Abstract: This study aimed to use nuanced statistical methods in a large UK sample to identify and explore the factors associated with different types of frequent user of Emergency Departments (EDs) who are referred to Mental Health Liaison Services (MHLS). A retrospective 5-year longitudinal study was conducted of all attenders ( n = 23, 718) of four London EDs who were referred to their MHLS. Longitudinal group-based trajectory analysis of monthly MHLS referrals enabled identification of factors which may contribute to membership of the resulting groups. Analysis revealed six clusters representing distinct attendance patterns; three clusters of these were identified as frequent attender groups (occasional, intermediate, heavy) containing 1119 people (4.7%). This 4.7% of the sample accounted for 24.2% of all admissions. Factors significantly related to membership of each of these groups were: having been involuntarily detained under the Mental Health Act, a higher number of care coordinators, and a diagnosis of substance abuse. The study revealed three clusters of frequent ED users with a MHLS referral who were more likely to have certain clinical and social care needs. A small proportion of clients identified as frequent users (4.7%) were responsible for nearly a quarter of all admissions (24.2%) during this timeframe. Highlights: 4.7% of frequent users were responsible for 24.2% of admissions during the timeframe. Six subsets of clients were identified, three of which were frequent attender groups. A limitation of this study is that the main reason for attending the ED was unavailable.